2006
DOI: 10.1095/biolreprod.106.053769
|View full text |Cite
|
Sign up to set email alerts
|

Primate Granulosa Cell Response via Prostaglandin E2 Receptors Increases Late in the Periovulatory Interval1

Abstract: Successful ovulation requires elevated follicular prostaglandin E2 (PGE2) levels. To determine which PGE2 receptors are available to mediate periovulatory events in follicles, granulosa cells and whole ovaries were collected from monkeys before (0 h) and after administration of an ovulatory dose of hCG to span the 40-h periovulatory interval. All PGE2 receptor mRNAs were present in monkey granulosa cells. As assessed by immunofluorescence, PTGER1 (EP1) protein was low/nondetectable in granulosa cells 0, 12, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 48 publications
6
30
0
Order By: Relevance
“…hCG treatment in vitro increased progesterone at all times as expected; the addition of fluprostenol with hCG did not alter progesterone when compared to hCG only. Moreover, fluprostenol did not alter media cAMP (not shown) or intracellular calcium when determined as previously described ((Markosyan et al 2006), not shown). Overall, PTGFRs in monkey granulosa cells were not localized to any specific region of the cell, and a selective PTGFR agonist did not alter progesterone production by granulosa cells obtained after the ovulatory stimulus.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…hCG treatment in vitro increased progesterone at all times as expected; the addition of fluprostenol with hCG did not alter progesterone when compared to hCG only. Moreover, fluprostenol did not alter media cAMP (not shown) or intracellular calcium when determined as previously described ((Markosyan et al 2006), not shown). Overall, PTGFRs in monkey granulosa cells were not localized to any specific region of the cell, and a selective PTGFR agonist did not alter progesterone production by granulosa cells obtained after the ovulatory stimulus.…”
Section: Resultssupporting
confidence: 65%
“…The cells were cultured on fibronectin-coated surfaces in chemically-defined, serum-free DMEM-Ham’s F12 medium containing insulin, transferrin, selenium, aprotinin, and human low-density lipoprotein as previously described (Markosyan et al 2006). The PTGFR agonist fluprostenol (1 μM; Cayman Chemical, Ann Arbor, MI), hCG (20 IU/ml, Sigma), the general cyclooxygenase inhibitor indomethacin (0.1 μM; Sigma), the phospholipase C (PLC) inhibitor U73122 (100 μM; Cayman), the protein kinase C (PKC) inhibitor Ro31-3220 (1 μM; CalBiochem, Billerica, MA), the mammalian target of rapamycin (mTOR) inhibitor rapamycin (1 μM; Invitrogen, Rockville, MD), the 3β-hydroxysteroid dehydrogenase inhibitor trilostane (250 ng/ml, Stegram Pharmaceuticals, Sussex, UK), progesterone (0.1 μM; Sigma), the aromatase inhibitor letrozole (4,4-[1,2,3-triazol-lyl-methylene]-bis-benzonitrite; 0.5 μM; Norvartis Pharm AG, Basel, Switzerland), estradiol benzoate (0.1 μM; Sigma), and the estrogen receptor antagonist ICI182,780 (1 μM; Tocris Biosciences, Bristol, UK) were added to cultures as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, total RNA obtained from granulosa cells was reverse transcribed using an oligo dT-anchor primer. cDNA was amplified by PCR with an PCR anchor and a gene specific forward primer for the EP3 common region (5'-TTATCAGGAGCGGAGAC-3') previously designed in our laboratory (Markosyan et al 2006). To obtain the full-length cDNA sequence of the EP3 common region, conventional PCR was performed using a forward primer 5'-GTAAACGCCGACCTCC-3' and a reverse primer 5'- GCAAAACTTTCGAAGAAGG-3'.…”
Section: Methodsmentioning
confidence: 99%
“…EP3 receptors were not detected in mock-transfected or empty vector-transfected CHO cells by immunocytochemistry using an EP3 antibody, following methods previously described by this laboratory (Markosyan et al 2006). Mock-transfected and empty vector-transfected CHO cells did not respond to PGE2 or sulprostone with alterations in intracellular calcium or cAMP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation